EFISIENSI PENGELOLAAN USAHA DAN PERHITUNGAN HARGA POKOK PRODUKSI SEBAGAI LANGKAH MENGOPTIMALKAN KEUNTUNGAN - Susano, Adhi; Rachmawati, Meida (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
Human resources are determinant in the wheels of business, so HR is required to be creative and innovative in developing strategies according to existing changes. One form of creating production efficiency is by calculating the cost of production using the ratio of raw materials in creating a low-cost finished product. Production efficiency is able to reduce costs so that the products produced are low-cost, which in the end the company is able to sell its products at lower prices as well. The calculation of the cost of production plays a very important role in determining the selling price of the product so that the set price can be competitive. In cost accounting, the function of calculating the cost of production is to determine, analyze and report the realization of cost items so that the financial reports can show reasonable data. Procurement of training activities by partnering with three rice mill business actors in Krangtowo Village in Demak City to provide training as well as guide business actors to be able to innovate in creating efficient rice production. The evaluation of this training is based on the understanding of the trainees in the given session. In addition, a questionnaire was also given which was filled in by participants to assess the quality of the training at the end of the session. From the training that was given enthusiastically and the participants' understanding was very good, this was evidenced from the questionnaire given at the end of the training session, the average understanding of the participants was on a scale of 4 which was included in the good category. So that the results of this training in the future must always be improved so that the understanding of village communities in managing finances and business management is even better.